2015
DOI: 10.1103/physreva.92.023401
|View full text |Cite
|
Sign up to set email alerts
|

K-shell photoionization ofO+andO2+ions: Experiment and theory

Abstract: Absolute cross sections for the single and double K-shell photoionization of carbonlike O 2+ and nitrogenlike O + ions were measured in the 526-620-eV photon energy range by employing the ion-photon merged-beam technique at the SOLEIL synchrotron radiation facility. High-resolution spectroscopy up to E/ E ≈ 5300 was achieved. Rich resonance structures observed in the experimental spectra are analyzed and identified with the aid of R-matrix and multiconfiguration Dirac-Fock (MCDF) methods. For these two atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 53 publications
5
37
0
Order By: Relevance
“…In systems like the z = 0 absorption toward Mrk 509, the entire line could be the O II Kβ line-12. Table III of Bizau et al 2015), their line strengths would be similar. In Table 2 we list the EWs of O II lines in Galactic sightlines from Nicastro et al (2016); errors are 1σ and upper limits are 3σ.…”
Section: O II Kβ "Line 12" Strength From Kαmentioning
confidence: 69%
“…In systems like the z = 0 absorption toward Mrk 509, the entire line could be the O II Kβ line-12. Table III of Bizau et al 2015), their line strengths would be similar. In Table 2 we list the EWs of O II lines in Galactic sightlines from Nicastro et al (2016); errors are 1σ and upper limits are 3σ.…”
Section: O II Kβ "Line 12" Strength From Kαmentioning
confidence: 69%
“…Combining with the single PI cross sections, we obtain the double PI cross sections. Our theoretical results are compared with the experiment of Bizau et al (2015) and we concluded that the DDAD processes of the final K-shell excited states are the origin of the double PI. We successfully diagnosed the population fraction of the prepared initial state in this experiment and interpreted the experimental results for the first time.…”
Section: Introductionmentioning
confidence: 75%
“…No data on the DDAD rates are available in the literature, to the best of our knowledge and thus we compare the natural lifetime widths with available experimental and theoretical results to evaluate the quality of our theoretical results. Our theoretical natural lifetime widths (fifth column), the measurements of Bizau et al (2015) (sixth column) and the previous available theoretical results (Zeng et al 2004;Bizau et al 2015;Garcia et al 2005) (seventh column) are given in (Bizau et al 2015). As the final state of the two resonance transitions is the same, the natural lifetime widths should, in principle, be nearly equivalent as the Auger decay rate is much larger than the radiative decay rate.…”
mentioning
confidence: 92%
See 2 more Smart Citations